The New Modes of Education System Due To Covid-19. - Neha Jaiswal; Dr.Kiran Gupta; Dr.Rashmi Pal (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
In present circumstance the world is in miserable condition from a global pandemic. This condition make the world stirring .In this pandemic people’s are facing many challange’s and many problems. Everyday need’s and work is miserably affecting. Peoples health, wealth and economy are in beneath position. Many sectors are effected by this disease. Many sector’s like -Education, defense, private sectors and MNC’s. The main aim of this report is to dwell some facts and data with the help of various records from the both government and private organization’s. And to provide some complacent manner. Due to COVID-19, in the education sector the students, the teacher’s and the parents of the students seeing a new era of education and they are the impetus of new modes of education. They are seeing and facing new structures and tactics which involve new generation technologies and methods of study. In this miserable condition the only hope of need is the rules and guidelines which are generated by W.H.O.It is hoped that this study will inform Students, Practitioners and Guardians for gaining the information related effects of Covid-19 in study. The new mode of education,the new system of education in front of the small primary student and graduate students.the new mode of exams and online teaching. the support of parents and the teachers. Keywords: dwell, miserable, complacent, stirring, beneath.